2011
DOI: 10.4103/0019-509x.75840
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in relation to gastric cancer progression

Abstract: Gastric cancer is a major cause of cancer death worldwide, especially in developing countries. The incidence of gastric cancer varies from country to country, probably as a result of genetic, epigenetic, and environmental factors. H. pylori infection is considered as a major risk factor in the development of gastric cancer. However, the scenario varies in Asian countries, exhibiting a higher rate of H. pylori infection and low incidence of gastric cancer, which could be attributed to strain-specific virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Hence, it could be deduced that H. pylori is present in the asymptomatic subjects but the virulent factors are expressed in a fraction of them. However, virulent strains may give rise to a plethora of gastric diseases when the suitable pathobiological conditions culminate in the gastric environment of the patients [27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it could be deduced that H. pylori is present in the asymptomatic subjects but the virulent factors are expressed in a fraction of them. However, virulent strains may give rise to a plethora of gastric diseases when the suitable pathobiological conditions culminate in the gastric environment of the patients [27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Even to the cases of non-gastrointestinal diseases, such as chronic cardiovascular disease, liver and biliary tract diseases and colorectal cancer, H. pylori also has a synergistic contribution[2]. In 1994 H. pylori was labeled as one of the first class cancer causing factors by the International Institute for Cancer Research[3]. Over half of the worldā€™s population are infected with H. pylori during their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori infection, the preneoplastic lesion chronic atrophic gastritis, intestinal metaplasia, free radicals, and familial GC predisposition have been identified as risk factors for GC. [6][7][8][9][10][11] Recently, studies have demonstrated that H. pylori infection may double the risk of stomach cancer. Infection with a particular type of H. pylori called cytoxin-associated antigen A (cagA)-positive H. pylori can increase the risk even more.…”
Section: Introductionmentioning
confidence: 99%